(untitled) (Journal of the Association for the Study of Australian Literature, 2011)
This paper positions the work of colonial poet Eliza Hamilton Dunlop amongst international Romantic poetry of the period, and argues that Dunlop’s poetry reflects a transposition of Romantic women’s poetry to Australia. Dunlop’s poetry, such as ‘The Aboriginal Mother’, demonstrates the relationship of Romantic women’s poetry to early feminism and Social Reform. As with the work of Felicia Hemans, Dunlop was interested in the role of women, and the ‘domestic’ as they related to broader national and political concerns. Dunlop seems to have been consciously applying the tropes, such as that of the mother, of anti slavery poetry found within American, British, and international poetic traditions to the Australian aboriginal context. Themes of indigenous motherhood, and also of Sati or widow burning in India, and human rights had been favored by early women’s rights campaigners in Britain from the 1820s, focusing on abolition of slavery through the identification of white women with the Negro mother. Dunlop’s comparative sympathy for the situation of aboriginals in Australia has been given critical attention as the aspect which makes her work valuable. However, in this essay I hope to outline how Dunlop’s poetry fits in to the international context of the engagement of Romantic women poets with Western Imperialist models and colonial Others.